Alternative investments based on the example of investments in wine from the Bordeaux region - Król, Patryk Janusz (Journal of Finance and Financial Law, 2025)
The purpose of the article. The article aims to indicate the economic conditions influencing the prices and distribution of Bordeaux wines on the European market, as well as to identify the key factors shaping their value. It raises the question of which aspects, including seasonality, quality, prestige, and consumer behavior, play a role in shaping the market for this unique good. Methodology. The study employs a literature review and secondary data analysis concerning Bordeaux wine prices. The methodology is based on the synthesis and description of conclusions from other authors, supplemented with a bibliometric analysis of literature from the Web of Science database covering the years 2001–2024. The bibliometric analysis aimed to identify major research trends and map the knowledge structure in the field of wine investment. Comparative analyses of prices across different seasons and quality categories were also conducted, taking into account factors such as vintage and region of origin. Statistical analyses were performed on the data to draw conclusions about the wine price dynamics over recent years. Results of the research. The research results indicate that the price of Bordeaux wines is influenced by both objective factors, such as quality and region of origin, and subjective factors, such as prestige and vintage. Seasonality was also found to play a significant role, affecting wine availability and prices at different times of the year. Ultimately, consumer preferences, especially among collectors and enthusiasts, significantly impact the market value of Bordeaux wine, underscoring the complexity of this market segment. Research hypothesis. The research hypothesis assumes that the investment value of Bordeaux wines is determined to a greater extent by the reputation and brand of the winery than by the objective quality of the product.